Immune deposits in extraglomerular vessels: their correlation with circulating immune complexes. - Burden, R P (1980)
Sixty-eight per cent of a consecutive series of 65 renal biopsies showed immune deposits in extraglomerular blood vessels. Although they occurred with a variety of clinical disorders and histological diagnoses, they were associated in particular with an acute nephritic syndrome, focal proliferative glomerulonephritis and non-specific mesangial changes. IgM was the commonest immunoglobulin class to be deposited and higher levels of IgM-containing complexes were detected in the serum of those patients with vascular deposits. Hitherto, immunofluorescent studies of renal biopsies have concentrated mostly on glomeruli but this study suggests that the extraglomerular vasculature deserves closer attention. The mechanisms for this pattern of localization are discussed.